SKEMA MURŪR SEBELUM TENGAH MALAM: Analisis Epistemologis terhadap Ijtihad Kementerian Agama RI dalam Fikih Haji - Adib, Muhammad (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2024)
This paper discusses the epistemological framework of ijtihad carried out by the Indonesian Ministry of Religion when establishing the murūr Muzdalifah scheme for elderly and disabled Hajj pilgrims. The focus is on the stipulated time for implementation, namely before midnight. With a normative-epistemological approach that relies on content analysis methods, this paper concludes that the Indonesian Ministry of Religion uses two ijtihad methods simultaneously, namely the istishlāhī and takhayyur methods. Using this method, the Indonesian Ministry of Religion selects and selects fatwas that are more appropriate to the conditions of the Hajj pilgrims and the situation in Muzdalifah and prioritizes the health and mental safety (hifzh al-nafs) of the Hajj pilgrims.